A Reply to John Bently Mays - Mallinson, Jean (Studies in Canadian Literature, 1978)
A response to John Bently Mays’ reply to Jean Mallinson’s article "Ideology and Poetry: An Examination of Some Recent Trends in Canadian Criticism."